Cysticercosis in Madagascar - Carod, Jean-François; Dorny, Pierre (The Journal of Infection in Developing Countries, 2020)
Introduction: Cysticercosis (CC) is the most common parasitic disease of the central nervous system. It is endemic in most developing countries where pigs are raised and consumed. An overview of all available data of this parasite in Madagascar is lacking. Methodology: We conducted a literature review, collecting information on published and available literature about cysticercosis in Madagascar between January 1st, 1990 and June 30th, 2020. Results: Out of 858 publications; 61 were included, issued from peer-review indexed journals, non-indexed journals, books, Ministry reports and press releases. In Madagascar, porcine cysticercosis has been reported since 1901; human cysticercosis is highly prevalent with an overall estimated seroprevalence between 7 and 21%. Serological analysis is based on Enzyme-Linked Immunosorbent Assay (ELISA) and Enzyme-linked immunoelectrotransfer blot techniques (EITB) for confirmative testing. Neurocysticercosis (NCC) is the most common pattern of cysticercosis in Madagascar and it is reponsible for pediatric morbidity causing more than 50% of epilepsy cases. Though CT-Scan is now available and tends to be considered the gold standard for NCC diagnosis, it remains unaffordable for most Malagasy patients and implies the proposal of a diagnostic algorithm for physicians. Conclusions: Our review has revealed that human taeniasis and bovine cysticercosis is a considerable burden in Madagascar. A national control program has been developed aiming to decrease the seroprevalence rate from 16 to 10% in 2015. The aim of the country is now to implement a CC control and elimination program. Meanwhile, some massive cysticercosis screenings have been conducted in the capital Antananarivo to drive people's attention on this widespread infection.